Pelatihan Pembuatan Short Movie untuk Kreativitas Siswa di Sekolah Menengah Atas - Nurdiyatnika, Rizal; Nurhadi, Zikri Fachrul (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The development of cinema today is quite numerous and varied with various types of films, such as short movies or commonly called short films that can be made by various groups ranging from young people to adults. Making a short movie or short film is a film that has a shorter duration so that it is not too difficult to make compared to a long film so that many people make it. SMAN 8 Garut is one of the schools that requires its students to make a short movie or short film as the final assignment of the students in class XII, but they are not equipped with a deeper understanding of short movie making considering that this school is not oriented towards vocational broadcasting and film like SMK. In order to overcome this problem, the film activist community Framemograph collaborated with students from the extracurricular Photography SMAN 8 Garut to create a short movie making training for students of SMAN 8 Garut. The purpose of this service is to equip students with knowledge and skills in making short movies or short films properly and correctly. This service method uses training with several stages including observation, preparation, and implementation. The results showed success where students were very active in asking questions to solve their problems or concerns in the process of making short movies or short films. Based on this success, it is hoped that students can apply the understanding they get in making short movies or short films later.